Starvation Affects the Muscular Morphology, Antioxidant Enzyme Activity, Expression of Lipid Metabolism-Related Genes, and Transcriptomic Profile of Javelin Goby (Synechogobius hasta) - Xiangning Chen; Yili Xu; Xiangyu Cui; Siying Zhang; Xiangqi Zhong; Juntao Ke; Yuze Wu; Zhiyu Liu; Chaoqing Wei; Zhujin Ding; Jianhe Xu; Hanliang Cheng (Aquaculture Nutrition)
Fish in natural and cultivated environments can be challenged by starvation. However, inducing starvation in a controlled manner cannot only reduce feed consumption but also reduces aquatic eutrophication and even improves farmed fish quality. This study investigated the effects of starvation on the muscular function, morphology, and regulatory signaling in javelin goby (Synechogobius hasta) by evaluating the biochemical, histological, antioxidant, and transcriptional changes in the musculature of S. hasta subjected to 3, 7, and 14 days fasting. The muscle glycogen and triglyceride levels in S. hasta were gradually reduced under starvation, reaching their lowest at the end of the trial (P<0.05). The levels of glutathione and superoxide dismutase were significantly elevated after 3–7 days of starvation (P<0.05), but later returned to the level of the control group. The muscle of starved S. hasta developed structural abnormalities in some areas after 7 days of food deprivation, and more vacuolation and more atrophic myofibers were observed in 14-day fasted fish. The transcript levels of stearoyl-CoA desaturase 1 (scd1), the key gene involved in the biosynthesis of monounsaturated fatty acids, were markedly lower in the groups starved for 7 or more days (P<0.05). However, the relative expressions of genes associated with lipolysis were decreased in the fasting experiment (P<0.05). Similar declines in the transcriptional response to starvation were found in muscle fatp1 and ppar γ abundance (P<0.05). Furthermore, the de novo transcriptome of muscle tissue from the control, 3-day and 14-day starved S. hasta generated 79,255 unigenes. The numbers of differentially expressed genes (DEGs) identified by pairwise comparisons among three groups were 3276, 7354, and 542, respectively. The enrichment analysis revealed that the DEGs were primarily involved in metabolism-related pathways, including ribosome, TCA pathway, and pyruvate metabolism. Moreover, the qRT-PCR results of 12 DEGs validated the expression trends observed in the RNA-seq data. Taken together, these findings demonstrated the specific phenotypical and molecular responses of muscular function and morphology in starved S. hasta, which may offer preliminary reference data for optimizing operational strategies incorporating fasting/refeeding cycles in aquaculture.